The Validity of an Ethnomathematics Based Student Worksheet Using Sekundang Batik Motifs in Plane Geometry Oriented to Contextual Teaching and Learning (CTL) - Marizka Purnamayana; Winda Ramadianti; Hilyati Milla (International Journal of Mathematics and Science Education, 2026)
Teaching plane geometry often faces challenges due to the abstract nature of geometric concepts, which are often detached from students’ real-life contexts. This study is a development research (Research and Development) using a modified 4D model reduced to 3D (Define, Design, Develop) aimed at producing and testing the validity of a Student Worksheet based on ethnomathematics with Batik Sekundang motifs on plane geometry material oriented toward Contextual Teaching and Learning (CTL). Validation was conducted by two mathematics education experts who assessed the feasibility of content/material, media, and language/readability using a Likert scale instrument. The data were analyzed quantitatively in a descriptive manner using percentage formulas to determine the level of validity. The results showed that the student worksheet obtained a validity percentage of 87.50% in content feasibility (very valid), 80.76% in media (valid), and 87.50% in language (very valid), with an overall average of 85.25%, which falls into the very valid category. Based on these results, the ethnomathematics-based student worksheet with Batik Sekundang motifs is declared suitable to be used as a supporting teaching material for contextual and meaningful plane geometry learning for students in South Bengkulu.